Women egalitarianism in the post-independence era; bane of societal immoralities - IYANDA, Rabiu (Al-Adab Journal, 2025)
The Subject of parenting and motherhood in African literary writings continues to be a major concern. The quest by many feminists African and other nationals looking for equal social opportunities between men and women has become prevalent in post-independence era writings. Some considered this move as the stimulant for societal vices assumed to be borne out of lack of parental care, and home training. Parenting/ home training is deemed not to be reserved in formal educational settings but only with parents at home. In the current age, where men and women strive for economic equality, women have no more time to play their feminine roles thereby subjecting their children to babysitters and crèches. This article examines the effects of African women in their struggle for economic power and the lack of time/energy to instill necessary and required knowledge in these younger ones with the probable effects on society. The paper highlights how to cope with the challenges caused by this negligence, using some available documents, novels and articles. Through a critical analysis, the article proffers promising solutions to curb the diffuse social reality.